2021
DOI: 10.1155/2021/6696606
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum Spore Polysaccharide Inhibits the Growth of Hepatocellular Carcinoma Cells by Altering Macrophage Polarity and Induction of Apoptosis

Abstract: Background. Ganoderma lucidum has certain components with known pharmacological effects, including strengthening immunity and anti-inflammatory activity. G. lucidum seeds inherit all its biological characteristics. G. lucidum spore polysaccharide (GLSP) is the main active ingredient to enhance these effects. However, its specific biological mechanisms are not exact. Our research is aimed at revealing the specific biological mechanism of GLSP to enhance immunity and inhibit the growth of H22 hepatocellular carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…TP-16 (EP4 antagonist) treatment polarized TAM from immunosuppressive M2 type to pro-inflammatory M1 type, which enhanced T-cell-mediated anti-tumor immunity and improved the efficacy of anti-PD-1 [ 58 ]. In addition, a series of studies have proved that Ganoderma lucidum spore polysaccharide (GLSP) [ 337 ], CMPB90-1 [ 338 ], natural M1 exosomes [ 339 ], conditional deletion of the microRNA (miRNA)-processing enzyme DICER [ 334 ] and TLR 7/8 agonist [ 57 ] can specifically eliminate M2-like phenotype or reset TAM from M2-like phenotype to M1-like phenotype to inhibit tumor development and reverse tumor treatment resistance.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…TP-16 (EP4 antagonist) treatment polarized TAM from immunosuppressive M2 type to pro-inflammatory M1 type, which enhanced T-cell-mediated anti-tumor immunity and improved the efficacy of anti-PD-1 [ 58 ]. In addition, a series of studies have proved that Ganoderma lucidum spore polysaccharide (GLSP) [ 337 ], CMPB90-1 [ 338 ], natural M1 exosomes [ 339 ], conditional deletion of the microRNA (miRNA)-processing enzyme DICER [ 334 ] and TLR 7/8 agonist [ 57 ] can specifically eliminate M2-like phenotype or reset TAM from M2-like phenotype to M1-like phenotype to inhibit tumor development and reverse tumor treatment resistance.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…[ 78 , 79 ]. Ganoderma lucidum spore polysaccharide (GLSP) promoted the polarization of primary macrophages into M1 type and cytokine expression (such as TNF-α, IL-1β, IL-6, and TGF-β1) [ 80 ].…”
Section: Polysaccharides In Different Liver Diseasesmentioning
confidence: 99%
“…APS, GLSP, fucoidan, Pleurotus ostreatus polysaccharide, ginger polysaccharide, Aconitum coreanum polysaccharide, pumpkin polysaccharide (PPPF), Rhizopus Nigrum polysaccharide, and an acid-soluble polysaccharide from Grifola frondose could inhibit hepatocellular carcinoma growth by apoptosis [ 78 , 79 , 80 , 85 , 86 , 87 , 88 , 89 , 90 ]. The JAK/STAT, PI3K/AKT, and RAS/ERKs pathways are enhanced in many HCC cells, conferring on them resistance to apoptotic stimuli [ 91 ].…”
Section: Polysaccharides In Different Liver Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact mechanism responsible for GLP-associated reduction in CD68 + macrophages needs to be illuminated in future studies. It was reported that GLP fostered primary macrophage polarization to M1 type and increased the production of TGF-β1, TNF-α, IL-1β, and IL-6 ( Song et al, 2021 ). GLP-intervened macrophages evidently repressed HCC cell proliferation by inducing cell cycle arrest and activating the mitochondrial apoptosis pathway via the PI3K/Akt signaling cascade.…”
Section: The Antitumor Activities Of Polysaccharides From G...mentioning
confidence: 99%